Cell cycle-resolved chromatin proteomics reveals the extent of mitotic preservation of the genomic regulatory landscape - Paul Adrian Ginno (Nature Portfolio, 2018)
Mitosis poses a challenge for transcriptional programs, as it is thought that several proteins lose binding on condensed chromosomes. Here, the authors analyze the chromatin-bound proteome through the cell cycle, revealing retention of most transcription factors and preservation of the regulatory landscape.